Supporting Information Visualization Research in an Academic Library: Lessons Learned from an Analysis of the Literature. - Groenendyk, Michael; Neugebauer, Tomasz (Information Technology & Libraries, 2024)
This paper summarizes librarian research on information visualization as well as general trends in the broader field, highlighting the most recent trends, important journals, and which subject disciplines are most involved with information visualization. By comparing librarian research to the broader field, the paper identifies opportunities for libraries to improve their information visualization support services.